Diseño de una herramienta para el análisis del golpe de ariete en tubería recta en un laboratorio de mecánica de fluidos (2019)
This project exposes the engineering development applied to the design of a tool for the analysis of water hammer in a straight pipe in a fluid mechanics laboratory, condensing knowledge acquired in both the petroleum engineering career and mechanical engineering. Initially, the theoretical basis for the occurrence of the water hammer phenomenon and specific cases in the oil industry were determined. Using the scoring method, an air chamber was chosen as a damping element and the detailed design was developed on this alternative. Also, the simulation phase on the water hammer generation and mitigation system was carried out with the Allievi program.